MARKET POWER, BANK-SPECIFIC FACTORS, AND MACROECONOMIC EFFECTS ON BANKING PROFITABILITY IN INDONESIA: BEFORE AND AFTER THE COVID-19 PANDEMIC - Hayet, Hayet; Hanafi, Syafiq Mahmadah; Afandi, Mukhammad Yazid (Fakultas Ekonomi dan Bisnis, UNTAN, 2024)
This paper examines the impact of market power, bank-specific factors, and macroeconomic changes on profitability in conventional and Islamic banking in Indonesia before and after the COVID-19 pandemic. The data was collected quarterly from 6 conventional banks and 6 Islamic banks during the period from the second quarter of 2014 to 2023, and analyzed using a panel data regression model approach. The dependent variable is bank profitability, measured using the return on asset proxy (ROA) and net interest margin (NIM) / net operating margin (NOM); while the independent variables are concentration ratio (CR), third-party funding (TPF), capital adequacy ratio (CAR), non-performing loan (NPL), operating expenses to operating income (BOPO ratio), gross domestic product (GDP), inflation, exchange rate, and dummy variables. The findings demonstrate that the COVID-19 pandemic has had a detrimental impact on both types of banking, with Islamic banking experiencing a more significant impact than the conventional banking. Furthermore, the TPF, BOPO ratio, exchange rate, and inflation have a comparable impact on the profitability in both types of banking. Similarly, the market power, NPL, CAR, and GDP have distinct impact on the two types of banking, demonstrating disparities in operational features and industry competitiveness levels.JEL: L16, E32, G21.